Perancangan Media Pembelajaran Berbasis AI Notebooklm pada Materi Teks Argumentasi: Berdasarkan Analisis Kebutuhan Siswa dan Guru pada Kelas IX SMP Negeri 4 Medan - Bonika Alprianta Sari Hulu; Dimas Bayu Kumbara; Dwi Ananda Putri; Faza Najmul Pasha; Friclia Dhea Lova Siagian; Gabriella Secilia Silitonga; Sarah Meutia; Ulyanti Pandiangan; Tri Indah Prasasti (Universitas 45 Surabaya, 2026)
The low interest and engagement of students in Indonesian language learning, particularly in argumentative text material, represents a fundamental issue that needs to be addressed through innovative learning media. This study aims to design an artificial intelligence (AI) based learning media using the NotebookLM platform for argumentative text material targeting ninth-grade students at SMP Negeri 4 Medan. The research employed a Research and Development (R&D) method using the ADDIE model, limited to the first three stages: analysis, design, and development. Data were collected through interviews with Indonesian language teachers and students to identify actual learning needs. The needs analysis revealed that students desired more varied, visual, and interactive learning experiences, while teachers continued to rely on conventional methods with minimal use of digital technology. Based on these findings, learning media were designed utilizing five main features of NotebookLM: infographics, presentation slides, concept maps, interactive quizzes, and flashcards. The resulting prototype was subsequently revised based on supervisor feedback, producing media that is more systematic, visually appropriate, and aligned with student needs. This study demonstrates that NotebookLM holds significant potential as an AI based alternative learning medium for Indonesian language instruction, capable of supporting more active, interactive, and student-centered learning at the junior high school level.